A systematic gray literature review: The technologies and concerns of microservice application programming interfaces - Chen, Fangwei; Zhang, Li; Lian, Xiaoli (Software, practice & experience, 2021)
The microservice application programming interface (API) becomes a growing concern in the IT industry, as a result of the increasing usage of microservice architecture style. There exist many successful practices among companies, communities, and so on. In contrast, the related academic research is still at an early stage, where lacks an overview of technologies for the design, implementation and operation of microservice APIs, as well as a general picture of concerns. In this article, we try to fill this gap by eliciting the technologies and concerns on microservice APIs and establishing a microservice API description model, with the intention of aiding researchers to gain an overview of this field and find possible research directions, and helping practitioners to better understand microservice APIs and be aware of the existing approaches for daily work. Twelve academic papers and 38 gray literatures are selected and analyzed following the systematic literature review approach. Besides, we give our observations from this study. For researchers, our findings show the most cared concerns of practitioners, and our description model can be used as a reference for new theories, experiments, and future research dimensions. For practitioners, our study can be used as a guideline for microservices experimentation and a starting point for practice.